Modeling Intelligent Health Care Using Multi-Agent System - Sarangi, Lokanath; Naryan Mohanty, Mihir (International Journal of Engineering and Technology, 2018)
Health monitoring can be automated through the help of multiple agents by data collection, coordination and storage. In this paper, we plan to organize our multi-agent architecture in two units. First one is the source unit, which contains smart wireless sensors and collection agent. The sensors read the vital signs from the patient’s body and they transfer the data to collection agent. The collection agent checks the received data whether it is redundant or not. The valuable medical data are then compressed and sent to updation agent in the destination unit. The updation agent updates the medical data into the database and physician. The physician gives the exact prescriptions for the received medical data with the help of medical history obtained from the database. The prescriptions are transferred to the database and transfer agent. The transfer agent transfers the prescriptions to corresponding collection agent after the compression process. The collection agent conveys the prescriptions to the patient after the decompression. Finally, the experimentation was made and we saved 1:5 of data by our proposed MAS system. Our implementation is done using JADE.